The Demise of the Nation State? - Tanzi, Vito (IMF Working Papers; Working Paper ;, 1998)
The globalization of economic activities that is characterizing many economies raises questions about the future of the nation state. This paper discusses this trend and shows that cross-frontiers spillovers have become more frequent and have increased the need for international agreements and international organizations to deal with them. It concludes that a continuation of current trends would increase the importance of subnational government while reducing (in the economic sphere) the importance of national governments.